2001
DOI: 10.1159/000051075
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Lymphatic Clearance of the Human Skin Using a Fluorescent Tracer

Abstract: The lymphatic clearance of the human skin at the instep of the foot was measured in 20 healthy volunteers (mean age ± SD 33.8 ± 10.5 years). Ten microliters of fluorescein isothiocyanate-dextran 150,000 were injected intradermally and the fluorescent light intensity of the deposit was measured 10 min and 24 h after injection by window densitometry. Fluorescent light intensity decreased by 31.2 ± 13.5 arbitrary units (p < 0.0001) or by a factor of 4.1 ± 3.9. Reproducibility was tested 2–6 weeks later in 7 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The extent of the contribution to the dispersion parameter from the lymphatic transport can be gained by simple analysis of data for the transport and clearance of isothiocyanate-dextran (MW=150 kDa) in human skin (24). Figure 2 in this work shows, as a consequence of lymphatic dispersion, isothiocyanatedextran spreads radially in the dermis a distance Δd≈ 0.3 cm (as approximated from the figure) after t=24 h following intra-dermal injection.…”
Section: Discussionmentioning
confidence: 83%
“…The extent of the contribution to the dispersion parameter from the lymphatic transport can be gained by simple analysis of data for the transport and clearance of isothiocyanate-dextran (MW=150 kDa) in human skin (24). Figure 2 in this work shows, as a consequence of lymphatic dispersion, isothiocyanatedextran spreads radially in the dermis a distance Δd≈ 0.3 cm (as approximated from the figure) after t=24 h following intra-dermal injection.…”
Section: Discussionmentioning
confidence: 83%
“…Several routes have been classified in the capillary wall structure as pathways available for exchange. Depending on the solutes size, nature and lipophilicity, they may prefer one or more of these pathways (Leu, 2001). Interendothelial cell junctions are the preferred pathway for the transport of hydrophilic solutes and also important for the small lipophilic solutes.…”
Section: Skin Drug Clearancementioning
confidence: 99%
“…Leu et al (46) reported on measurement of lymphatic clearance of the human skin of the foot in 20 subjects. 0.01 ml of FITC–dextran was injected intradermally.…”
Section: Human Safety and Adverse Effects After Various Intradermal Umentioning
confidence: 99%